Qualitative Analysis of Water Contents in The Refill Drinking Water Depot Of Giripurno Village, Bumiaji, Batu - Peni Ambar Wati; Anugerah Dany Priyanto; Yehezkiel Flobert Silaban; Devara Priya Ganendra (Universitas Muhammadiyah Sidoarjo, 2022)
Indonesia Central Statistics Agency shows that refilled water will be the main source of drinking water that is most widely used by households in Indonesia in 2020. In particular, people who live close to clean water sources such as Giripurno Village, Bumiaji District, Batu City feel that bottled water is getting more expensive, so that another alternative is emerging, namely drinking water produced by Water Depot Refilling Station (DAMIU), which is more affordable, but the quality is unknown. Therefore, drinking water at the refill drinking water depot is analyzed based on physical, chemical, and microbiological aspects to see the feasibility of refilled drinking water in accordance with PERMENKES No. 492 of 2010 about Drinking Water Quality Requirements. Drinking water samples were taken once at the refill drinking water depot. The results of laboratory analysis of drinking water are measured in terms of physical, chemical and microbiological parameters according to the Indonesian National Standard (SNI) method. The results of the analysis of the DAMIU in Giripurno Village sourced from the Kijan Spring is accordance with the PERMENKES RI Number 492/MENKES/PER/IV/2010 except for Coliform levels, so further research needs to be done to eliminate excessive Coliform levels.